THE SYNERGISTIC ROLE OF DIVERSITY, EQUITY, AND INCLUSION (DEI) IN ADVANCING ORGANIZATIONAL SUSTAINABILITY: A STRUCTURED REVIEW - Ki Yen Ping, (Malaysian Journal of Business and Economics (MJBE), 2025)
Diversity, equity, and inclusion (DEI) are essential for long-term organizational success, yet their direct impact on sustainability remains unclear. This systematic review examines DEI’s role in sustainable business practices by analysing 31 peer-reviewed articles published within 2022–2024 through qualitative analysis. Findings reveal that companies with strong DEI policies achieve more significant innovation, higher employee satisfaction, and improved financial performance, enhancing sustainability. Notably, 75% of studies report a strong positive link between DEI and sustainable outcomes. The review underscores DEI as a core driver of business success and encourages organizations to integrate DEI into their strategies. It also provides insights and recommendations for future research and practical implementation.